FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEJANG DEMAM BERULANG PADA ANAK BALITA DI RSUD BEKASI - Helena Golang Nuhan (AKPER Pasar Rebo, 2020)
Background: Febrile seizures are seizures that often occur in children under five. After the first febrile seizure, the child can recur one to three times. Research goal : was to determine the factors associated with the occurrence of recurrent febrile seizures of children under five in RSUD. Bekasi. Research Methods: The study design uses descriptive analytic with Cross Sectional approach, conducted in April 2018 and using purposive sampling. Results: Of the 106 respondents, 72% of recurrent febrile seizures occurred in children under the age of 0-24 months, 73.8% were male, 74.7% had a family history of febrile seizures, 67.6% had a family history of epilepsy. 76.7% experienced an increase in body temperature ≥37.5oC, and 75.3% experienced a type of complex febrile seizure. There was a significant relationship between age, sex, history of febrile seizures, body temperature and type of febrile seizure (P = 0.003, P = 0.007, P = 0.003, P = 0.001, P = 0.002). There was no significant relationship between epilepsy history (P = 0.977) and the incidence of recurrent febrile seizures in children under five. Conclusion: Fever that is not treated properly can cause serious complications in children under five.